2017
DOI: 10.1111/mec.14093
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian species identification under the multispecies coalescent provides significant improvements to DNA barcoding analyses

Abstract: DNA barcoding methods use a single locus (usually the mitochondrial COI gene) to assign unidentified specimens to known species in a library based on a genetic distance threshold that distinguishes between-species divergence from within-species diversity. Recently developed species delimitation methods based on the multispecies coalescent (MSC) model offer an alternative approach to individual assignment using either single-locus or multiloci sequence data. Here, we use simulations to demonstrate three feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 31 publications
0
58
0
Order By: Relevance
“…Setting the clustering threshold to 100% yielded 1572 MOTUs, 99% yielded 824 MOTUs, and 97% yielded only 287 MOTUs. The low number of MOTUs obtained using the 97% clustering threshold is likely the result of multiple species being grouped together into the same MOTU as 3% divergence far exceeds interspecific variation in many genera (Yang and Rannala, 2017). Setting the clustering threshold to 100%, on the other hand, likely resulted in more than one MOTU being formed for a single taxonomic species as a result of infraspecific variation and/or sequencing errors between reads.…”
Section: Resultsmentioning
confidence: 99%
“…Setting the clustering threshold to 100% yielded 1572 MOTUs, 99% yielded 824 MOTUs, and 97% yielded only 287 MOTUs. The low number of MOTUs obtained using the 97% clustering threshold is likely the result of multiple species being grouped together into the same MOTU as 3% divergence far exceeds interspecific variation in many genera (Yang and Rannala, 2017). Setting the clustering threshold to 100%, on the other hand, likely resulted in more than one MOTU being formed for a single taxonomic species as a result of infraspecific variation and/or sequencing errors between reads.…”
Section: Resultsmentioning
confidence: 99%
“…The MSC model‐based species delimitation approach seems useful for delineating putative species, as it outperforms the simple distance threshold‐based DNA barcoding methods (Yang & Rannala, ). However, a simulation‐based study found that the MSC species delimitation approach identifies genetic structure rather than species, resulting in an inflated estimation of the number of species (Sukumaran & Knowles, ).…”
Section: Discussionmentioning
confidence: 99%
“…The MSC model-based species delimitation approach seems useful for delineating putative species, as it outperforms the simple distance threshold-based DNA barcoding methods (Yang & Rannala, 2017).…”
Section: Species Delimitation and Determination Of Otusmentioning
confidence: 99%
“…We retained all singleton cytb haplotypes for these analyses (i.e. haplotypes that were represented by one sample), as BPP has been shown to be robust to the inclusion of species represented by a single individual [65]. Following standard approaches [16, 66] we conducted four BPP analyses using different combinations of diffuse population size (θ) and divergence time (τ) priors to evaluate the sensitivity of analyses to variation in these parameters.…”
Section: Methodsmentioning
confidence: 99%